2016
DOI: 10.1097/brs.0000000000001233
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Cortical Bone Trajectory Screw Compared With Standard Trajectory Pedicle Screw

Abstract: The standard pedicle screw had a better fatigue performance compared with the CBT screw in vertebra with compromised bone quality. The proper insertion of the CBT screw might be prevented by the laminar anatomy depending on the screw head design. The CBT screw damaged the bone along its shaft by rotating around a fulcrum, located at either the pars, pedicle isthmus, or the junction of the pedicle and superior endplate, contingent upon the strength of the bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…[41] reported equivalent mechanical xation properties of both approaches in their cadaveric biomechanical study including pull-out and toggling testing. Contrary results were achieved by Akpolat et al [1], who stated that non-augmented TT screws had a better fatigue performance compared to CBT screws in vertebrae of compromised bone quality. As the use of bone cement during posterior instrumentation of the osteoporotic spine represents the gold standard, augmented TT screws were compared to possible alternatives within this study.…”
Section: Discussionmentioning
confidence: 71%
“…[41] reported equivalent mechanical xation properties of both approaches in their cadaveric biomechanical study including pull-out and toggling testing. Contrary results were achieved by Akpolat et al [1], who stated that non-augmented TT screws had a better fatigue performance compared to CBT screws in vertebrae of compromised bone quality. As the use of bone cement during posterior instrumentation of the osteoporotic spine represents the gold standard, augmented TT screws were compared to possible alternatives within this study.…”
Section: Discussionmentioning
confidence: 71%
“…These authors determined, in a multiple regression analysis, that BMD of the femoral neck, screw length within the lamina, and cephalad angle were significant independent factors affecting the torque [ 21 22 ]. However, in contradiction to previous articles, Akpolat et al [ 23 ] published in 2016 the results of a cadaveric study which concluded that implantation via TT required more cycles for screw loosening and showed better resistance to pullout. Finally, Sansur et al [ 24 ] compared CBT and TT in destabilized cadaveric lumbar spines with osteoporosis, showing that CBT gave better results in the lower spine because of an increase in cancellous bone limit fixation with TT ( Table 2 ) [ 3 14 15 16 17 18 19 21 22 23 24 25 26 ].…”
Section: Resultsmentioning
confidence: 86%
“…11 The relationship with osteoporosis and cortical bone purchase requires further cautious investigation as well. 15 Our biomechanical study included the lumbar spine. Segmentspecific individual anatomical variance and sagittal curvature in respect to gravity could provide a unique vector environment that may affect the long-term stability of the spondylodesis.…”
Section: Discussionmentioning
confidence: 99%